IDEOLOGY OG MYTH IN JAVANESE TRADITION TINGKEBAN - Selvia Handayani; Widya Andayani (TRANSFORM : Journal of English Language Teaching and Learning, 2020)
This research is aimed to analyze the ideology of myth in the equipments used in tingkeban ceremony by using the theory from Martin. The data of this research are taken from the Javanese Tingkeban ceremony presented in Desa Sei Buluh. This study is focused in the process and equipments used in tingkeban ceremony and then analyzing the myth with the meaning of each equipment. The writer conclude if there are 12 equipments which contain of myths and two rituals. Every equipment has its myth that have same purpose that is to throw away dangers of the children and the prospective mother. The ideology of myth in each procession and equipments related to the animism and dynamism belief system that roh (spirit) can benefit human life, as well as can asked for help for human life in this world, and belief that every object, plant or animal has magical powers that can disturb or protect humans. This research is related to the academic study of symbolism as guidance to live a new life in Javanese culture. That tingkeban ceremony is using a variety of tools and devices that are symbolized by jarwa dhosok which is a term in the traditional Javanese society. Tools and equipment are believed to mean more than just an object by its adherents.